Kant and the metaphysics of causality - Watkins, Eric, 1964- (Cambridge University Press, 2005)
This is a book about Kant's views on causality as understood in their proper historical context. Eric Watkins argues that a grasp of Leibnizian and anti-Leibnizian thought in eighteenth-century Germany helps one to see how the Critical Kant argued for causal principles that have both metaphysical and epistemological elements.